A net-zero emissions energy system in India by 2050: An exploration. (10th June 2022) - Vats, Garima; Mathur, Ritu
Abstract: This study examines whether adequate opportunities exist for full decarbonisation of the Indian energy sector and highlights where enough choices for full decarbonisation by 2050 do not exist. The study suggests transformative levels of electrification, energy efficiency improvements, and a switch towards decarbonised fuels (largely green hydrogen, decarbonised electricity, and bioenergy) as the three mainstays of India's decarbonisation strategy that could plausibly shift the energy sector towards a net-zero emissions future. The study also indicates that the heavy freight and industrial sectors face challenges in achieving full decarbonisation because of a lack of adequate technological solutions. Accordingly, residual emissions of about 1.3 gigatonnes in the system would require carbon sequestration options, including both technological and nature-based solutions, to achieve net-zero emissions. This study is expected to encourage further deliberations and deep dives into energy sub-sectors, which would benefit planners and policymakers in delineating India's sustainable energy transition strategy. Highlights: Analysis of decarbonisation potential of Indian energy sector. Transformative electrification, EE improvements & decarbonised fuels would be needed. Bio-energy, Green hydrogen, and decarbonised electricity as key decarbonising fuels. Despite pushing technological limits, around 1.3 Gt of CO2 e emissions remain. Sequestration options needed to enable energy sector's NZE transition.